Pembuatan Feed Instagram sebagai Media Promosi untuk Meningkatkan Brand Awareness pada UMKM Hataraya Food Kota Malang - Amanda Yogi Febrianita; Ahmad Fauzi; Dwi Sudjanarti (Indo Publishing, 2026)
The growth of social media has made Instagram one of the most popular digital promotional media used by MSMEs to increase brand awareness. Hataraya Food has used Instagram as a promotional medium, but its feed management has not been optimal, resulting in inconsistent visuals, unclear product information, and low audience engagement. This study aims to create an Instagram feed as a promotional medium, measure its feasibility based on content quality dimensions, and analyze its effectiveness in increasing the brand awareness of Hataraya Food. This study used the action research method with a descriptive quantitative approach conducted through two cycles, each consisting of planning, action, observation, and reflection. The population consisted of the audience and prospective consumers of Hataraya Food, with a purposive sample of design experts, marketing experts, and prospective consumers as questionnaire respondents. Data were analyzed using a Likert scale and mean score to measure content quality based on six Kingsnorth dimensions, and the RACE model (Reach, Act, Convert, Engage) together with Engagement Rate to measure effectiveness. The study produced 9 Instagram feed contents published according to a content calendar. Content quality testing showed that all dimensions were in the Very Good category, so the feed was considered feasible as a promotional medium. RACE effectiveness measurement showed scores of 4.51 for Reach, 4.47 for Act, 4.44 for Convert, and 4.51 for Engage, all in the Very Good category. The feed implementation also increased the account reach, impressions, interactions, and followers of the Hataraya Food Instagram account. This study concludes that the developed Instagram feed is effective as a promotional medium in increasing the brand awareness of Hataraya Food, so that consistency of visual design and content planning should be continuously maintained.